Think tanks and education. FAES neoliberalism in the LOMCE - Geo Saura (Arizona State University, 2015)
The article focuses attention on the discourses of the Spanish neoliberal think tank Foundation for Social Studies and Analysis (FAES) of the conservative Popular Party (PP). This neoliberal think tank is the main group of actors that produce a deconstructive logic of the Spanish public welfare system to construct a complex set of neoliberal policies. The analysis is developed in the educational policy field to understand the narratives of the Spanish Educational Reform Act. The text is divided into four sections. First, from a theoretical dimension, it addresses different perspectives to analyze the neoliberalism and the processes of privatization in the public education. The second, from a theoretical review, it addresses the new role that think tanks occupy and their advocacy in the design of neoliberal policies. The third, through a socio-historical analysis, reviews how throughout the democratic period (1978) the different Spanish political forces have incorporated mechanisms of endogenous privatization in education as a firm commitment to restructure "the public." The fourth section discusses how the discourses of FAES, extracted from the Web of foundation, articles, books and videos of participants of this think tank, have been used to introduce various mechanisms of hidden privatization in the Spanish educational system, and its commissioning is consolidated by means of the current Educational Reform Act (LOMCE).